2021
DOI: 10.1007/s00402-021-03873-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality in older patients sustaining pelvic or acetabular fractures

Abstract: Introduction This study aimed to investigate potential factors, including delay to surgical stabilisation, affecting mortality in older patients sustaining pelvic or acetabular (PA) fractures. Materials and methods A retrospective review of the Trauma Audit and Research Network (TARN) database was performed to identify older patients (aged 65 and over) sustaining PA fractures treated surgically in a UK Major Trauma Centre (MTC) between 2015 and 2019. Chi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Central to the ambiguity is the fact that there is not established definition for "early" fixation in the literature, as the range has varied from < 24 h to 15 days from injury [9,10]. More recent literature favors earlier surgical treatment [11][12][13] (Table 1.) Studies demonstrate early fixation can reduce morbidity in unstable PAF patients.…”
Section: Time To Fixationmentioning
confidence: 99%
See 2 more Smart Citations
“…Central to the ambiguity is the fact that there is not established definition for "early" fixation in the literature, as the range has varied from < 24 h to 15 days from injury [9,10]. More recent literature favors earlier surgical treatment [11][12][13] (Table 1.) Studies demonstrate early fixation can reduce morbidity in unstable PAF patients.…”
Section: Time To Fixationmentioning
confidence: 99%
“…Enninghorst et al further concluded that ORIF of unstable pelvic ring fractures is safe within 6 h. Ding et al reviewed 791 acetabular fractures and found that increased time to fixation was associated with increased risk of infection with incidence as high as 40% with > 10 days of delay, compared to 15% for > 2 days of delay [15]. However, evidence suggests that there is no significant difference in 30-day, 60-day and 1-year mortality rates between geriatric PAF patients operated on within < 72 h compared to those operated on > 72 h [12,13] Furthermore, delays in surgical fixation have been shown to significantly reduce the quality of fracture reduction [16,17]. Using logistic regression analysis, Dailey et al showed that each day without operative intervention decreased the odds of anatomic reduction by 12% [17].…”
Section: Time To Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic or acetabular fractures are rare injuries compared to fractures in other regions of the body, representing only about 3–8% of all fracture cases and associated with a high mortality rate of about 4–28% [ 1 ]. Pelvic fractures are one of the main results of low energy trauma such as falls, particularly in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Level of evidence: Prognostic Level III F ractures of the acetabulum (AO/OTA 62A-C) in the elderly are associated with prolonged hospital stays, perioperative complications, 30-day mortality of between two and seven percent, and 1-year mortality rates of between and eight and 20%. [1][2][3][4][5] Treatment can be nonsurgical or surgical. Surgical treatment options include open reduction and internal fixation (ORIF), closed reduction and percutaneous fixation, total hip arthroplasty (THA), and combined ORIF-THA.…”
mentioning
confidence: 99%